MRI Study of Brain Development and IQ - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Volumetric analysis of brain images obtained from MRI was used to study cerebral development in 85 normal children and adolescents, 5 to 17 years of age, at the Kennedy Krieger Institute, Johns Hopkins University, Baltimore; and Thomas Jefferson School of Medicine, Philadelphia, USA.